2019
DOI: 10.1101/728659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence and diversification of a host-parasite RNA ecosystem through Darwinian evolution

Abstract: A crucial problem for primitive replicators before the origin of life is the appearance of parasitic or selfish replicators, which destabilize molecular cooperation and prevent the development of complexity. To date, theoretical and experimental studies have indicated that spatial structures, such as cell-like compartments, support sustainable replication of primitive replicators even in the presence of parasites. However, it is still a mystery how these host and parasitic replicators can evolve when they unde… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 60 publications
(86 reference statements)
2
29
0
Order By: Relevance
“…First, the irregularly changing host and parasitic RNA concentrations in the early stage turned into a relatively regular oscillation in the late stage. Second, parasitic RNAs with different lengths (~ 220 nt, ~1100 nt, and ~500 nt) newly appeared only in the early stage, as reported previously 29 , and ~500 nt parasitic RNAs dominated the population throughout the late stage, although a small amount of ~220 nt RNAs was detected transiently (at rounds 136-140, 147-151, 178-181, and 207-210). These results suggested that the mode of evolution changed in the late stage.…”
Section: Long-term Evolution Of An Rna Replicatorsupporting
confidence: 75%
See 3 more Smart Citations
“…First, the irregularly changing host and parasitic RNA concentrations in the early stage turned into a relatively regular oscillation in the late stage. Second, parasitic RNAs with different lengths (~ 220 nt, ~1100 nt, and ~500 nt) newly appeared only in the early stage, as reported previously 29 , and ~500 nt parasitic RNAs dominated the population throughout the late stage, although a small amount of ~220 nt RNAs was detected transiently (at rounds 136-140, 147-151, 178-181, and 207-210). These results suggested that the mode of evolution changed in the late stage.…”
Section: Long-term Evolution Of An Rna Replicatorsupporting
confidence: 75%
“…S1). We conducted 120 rounds of the transfer cycle (rounds 1-120) in the previous studies 28,29 and additional 120 rounds (rounds 121-240) in this study.…”
Section: Long-term Evolution Of An Rna Replicatormentioning
confidence: 99%
See 2 more Smart Citations
“…By studying the sequence information of the replicase and its parasites, they suggested that parasites can take an active part in the evolution of their host and not just in their own. Different sub-populations of parasites can appear, forming an ecosystem [22], which accelerates evolution. Future studies are needed to quantify these co-evolutionary mechanisms, and perhaps our model could help in that task.…”
Section: Discussionmentioning
confidence: 99%